"Re-placed" - Reconsidering relationships with place and lessons from a pandemic. (December 2020) - Devine-Wright, Patrick; Pinto de Carvalho, Laís; Di Masso, Andrés; Lewicka, Maria; Manzo, Lynne; Williams, Daniel R.
Abstract: The Covid-19 pandemic has prompted a reconsideration, perhaps even a fundamental shift in our relationships with place. As people worldwide have experienced 'lockdown, ' we find ourselves emplaced in new and complex ways. In this Commentary, we draw attention to the re-working of people-place relations that the pandemic has catalysed thus far. We offer insights and suggestions for future interdisciplinary research, informed by our diverse positionalities as researchers based in different continents employing diverse approaches to people-place research. The article is structured in two sections. First, we consider theoretical aspects of our current relationships to place by proposing a framework of three interdependent axes: emplacement-displacement, inside-outside, and fixity-flow. Second, we identify six implications of these dialectics: for un-making and re-making 'home'; precarity, exclusion and non-normative experiences of place; a new politics of public space; health, wellbeing and access to 'outside' recreational spaces; re-sensing place, virtual escapes and fluid places, and methodological and ethical considerations. Across these topics, we identify 15 key questions to guide future research. We conclude by asserting that learning lessons from the global pandemic is necessarily tentative, requiring careful observation of altered life circumstances, and will be deficient without taking relationships with place into account. Highlights: We draw attention to the re-working of people-place relations that the pandemic has catalysed globally. We propose a conceptual framework of three dialectics: emplacement-displacement, inside-outside, and fixity-flow. We identify six implications of these dialectics and offer 15 key research questions. Learning lessons from the pandemic requires careful observation of altered life circumstances.